Direct ubiquitination of pattern recognition receptor FLS2 attenuates plant innate immunity - Lu, Dongping (2011)
Innate immune responses are triggered by the activation of pattern-recognition receptors (PRRs). The Arabidopsis PRR FLS2 senses bacterial flagellin and initiates immune signaling by association with BAK1. The molecular mechanisms underlying the attenuation of FLS2 activation are largely unknown. We report that flagellin induces recruitment of two closely related U-box E3 ubiquitin ligases PUB12 and PUB13 to FLS2 receptor complex in Arabidopsis. BAK1 phosphorylates PUB12/13 and is required for FLS2-PUB12/13 association. PUB12/13 polyubiquitinate FLS2 and promote flagellin-induced FLS2 degradation, and the pub12 and pub13 mutants displayed elevated immune responses to flagellin treatment. Our study has revealed a unique regulatory circuit of direct ubiquitination and turnover of FLS2 by BAK1-mediated phosphorylation and recruitment of specific E3 ligases for attenuation of immune signaling.